The Influence of Corporate Governance, Factors Of Auditors, And Gender Diversification on Integrity of Financial Statements - Riski Etika Etika Suhendra (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
This research aims to determine the influence of corporate governance, audit quality, industry specialisation of auditors, and gender diversification on the integrity of financial statements, both simultaneously and partially. The population in this research is the entire sub-sector property and real estate company listed on the Indonesia Stock Exchange in 2016-2018. The sample determination in this study used purposive sampling and obtained 96 samples. Data analysis uses descriptive statistical analysis and logistic regression analysis. The results showed that corporate governance, audit quality, industry specialization of auditors, and gender diversification are the simultaneous effect on the integrity of financial statements. Partially, the industry's specialty of auditors has a negative effect on the infidelity of financial statements, while corporate governance, audit quality, and gender diversification have no effect on the integrity of financial statements.